Statin Treatment and Carotid Plaque Composition: A Review of Clinical Studies - Puato, Massimo; Zambon, Alberto; Faggin, Elisabetta; Rattazzi, Marcello; Pauletto, Paolo (Current Vascular Pharmacology, 2014)
The impact on cardiovascular events achieved by statin therapy seems to be mostly attributable to their cholesterol- lowering effect, with a highly debated contribution of the lipid-independent pleiotropic effects. Statins have an established role in the treatment of hypercholesterolemia with a clear and robust reduction in cardiovascular morbidity and mortality. Nevertheless, the pathophysiologic effect of statins on inflammatory responses and local atherosclerotic plaque morphology in humans remains a matter of debate. In particular, the question remains whether statin-induced alterations in plaque composition can be ascribed mainly to low density lipoprotein cholesterol (LDL-C) lowering or an antiinflammatory pleiotropic effect, or both. This review summarizes the available evidence of the effects of statins on carotid plaque cellular composition in clinical settings, focusing on lipid-related and lipid-independent effects of statin therapy. A systematic review of the web online databases was performed. Studies in humans evaluating the effect of statins on composition of carotid plaque removed at endarterectomy were eligible for inclusion. Data support the view that plaque composition even after a short-term lipid lowering therapy is significantly modulated by the degree of LDL-C lowering. A contribution of LDL-C independent, anti-inflammatory mechanisms of statins on plaque stability is only suggested by some of the studies. Actually, data strongly support the current guidelines based on progressively lower LDL-C targets depending upon the cardiovascular risk of individual patients.
Keywords: Carotid arteries